Gene Therapy in the Light of Lifestyle Diseases: Budesonide, Acetaminophen and Simvastatin Modulates rAAV Transduction Efficiency - Żaneta Słyk; Natalia Stachowiak; Maciej Małecki (MDPI AG, 2024)
Recombinant AAV (rAAV) vectors are increasingly favored for gene therapy due to their useful features of vectorology, such as transfection of dividing and nondividing cells, the presence of tissue-specific serotypes, and biosafety considerations. This study investigates the impact of commonly used therapeutic drugs-acetaminophen, budesonide, and simvastatin-on rAAV transduction efficiency in HEK-293 cells. Cells were transduced with an AAV mosaic vector under the control of a cytomegalovirus (CMV) promoter encoding green fluorescent protein (GFP). Transduction efficiency was assessed by qPCR and fluorescent microscopy. Analysis of functional interactions between genes potentially involved in rAAV transduction in drug-exposed cells was also performed. This study showed a clear effect of drugs on rAAV transmission. Notably, acetaminophen enhanced transduction efficiency by 9-fold, while budesonide and simvastatin showed 2-fold and 3-fold increases, respectively. The gene analysis illustrates the possible involvement of genes related to cell membranes in the potentiation of rAAV transduction induced by the drugs under investigation. Attention should be paid to S100A8, which is a common drug-modified gene for drugs showing anti-inflammatory effects (budesonide and simvastatin), demonstrating an interaction with the gene encoding the receptor for AAV (HGFR). This study underscores the significance of assessing rAAV pharmacokinetics/pharmacodynamics (PKs/PDs) and drug-gene therapy interactions in optimizing gene therapy protocols.